Brewing and Distilling Yeasts - Stewart, Graham G (Springer, 2020)
1: Introduction. 2: History of Brewing and Distilling Yeast. 3: Taxonomy of Brewing and Distilling Yeasts and Methods. 4: Yeast Culture Collections, Strain Maintenance and Propagation…